2021
DOI: 10.1002/ange.202016395
|View full text |Cite
|
Sign up to set email alerts
|

Post‐Functionalization of Supramolecular Polymers on Surface and the Chiral Assembly‐Induced Enantioselective Reaction

Abstract: Although post-functionalization is extensively used to introduce diverse functional groups into supramolecular polymers (SPs) in solution, post-functionalization of SPs on surfaces still remains unexplored. Here we achieved the onsurface post-functionalization of two SPs derived from 5,10,15-tri-(4-pyridyl)-20-bromophenyl porphyrin (Br-TPyP) via cross-coupling reactions on Au(111).T he ladder-shaped, Cu-coordinated SPs preformed from Br-TPyP were functionalized through Heck reaction with 4-vinyl-1,1'-biphenyl.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 70 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Thus, understanding reactant selectivity is particularly crucial in reaction chemistry. High reaction selectivity is beneficial to improve the yield of target products such as drugs, thereby effectively reducing the waste of raw materials and environmental pollution and the cost of drug production, improving the ecological environment. To date, one of the major challenges in this field is to explore the mechanism of reactant selectivity, which necessitates an appropriate characterization method and model system. As an alternative to conventional chemistry, surface-assisted nanomaterial synthesis under ultra-high-vacuum (UHV) conditions has attracted tremendous researchers’ attention, which allows sample characterization of reaction intermediate products by surface techniques such as scanning probe microscopy (SPM). Unlike in solution, the selectivity of reactants on surfaces is affected by many factors, such as supramolecular templating effects, substrate templating effects, kinetic and dynamic effects, and molecular steric hindrance. Based on the SPM technique, several meaningful studies related to selectivity have been reported on metal surfaces. …”
Section: Introductionmentioning
confidence: 99%
“…Thus, understanding reactant selectivity is particularly crucial in reaction chemistry. High reaction selectivity is beneficial to improve the yield of target products such as drugs, thereby effectively reducing the waste of raw materials and environmental pollution and the cost of drug production, improving the ecological environment. To date, one of the major challenges in this field is to explore the mechanism of reactant selectivity, which necessitates an appropriate characterization method and model system. As an alternative to conventional chemistry, surface-assisted nanomaterial synthesis under ultra-high-vacuum (UHV) conditions has attracted tremendous researchers’ attention, which allows sample characterization of reaction intermediate products by surface techniques such as scanning probe microscopy (SPM). Unlike in solution, the selectivity of reactants on surfaces is affected by many factors, such as supramolecular templating effects, substrate templating effects, kinetic and dynamic effects, and molecular steric hindrance. Based on the SPM technique, several meaningful studies related to selectivity have been reported on metal surfaces. …”
Section: Introductionmentioning
confidence: 99%
“…On-surface chemoselectivity is the key to realize highquality target nanostructures with a minimum of possible side products. Many strategies can be used to gain chemoselectivity control to some extent, such as supramolecular templating effects [16,[28][29][30][31], substrate templating effects [15,[32][33][34][35], kinetic and dynamic effects [36][37][38], and molecular steric hindrance [39][40][41][42][43]. Although chemoselectivity has been demonstrated in many systems before, it is always desirable to explore new strategies to extend the on-surface synthesis toolbox and design novel nanostructures with tailored properties.…”
Section: Introductionmentioning
confidence: 99%